Kajian Semiotika Riffatere Dalam Lagu Hitchcock Karya Yorushika - Rizkya Putri Utami (Universitas Katolik Widya Karya Malang, 2023)
Songs are included in the type of literary works of poetry. Song lyrics are written in poetic language so that they are classified as literary works of poetry. songs consist of many types. In this study the songs that became the object of research were J-Pop songs. J-Pop is a pop genre song originating from Japan. The song that is the object of research is a song that was famous at that time. Not only booming in their home country but covering many other countries as well. the fact that youth is the most turbulent period in the stages of human life is the inspiration for this song. The song, entitled Hitchcock by yorushika, was published to the wider community via YouTube in 2018. The theory that serves as the basis for this research is Riffatere's theory of semiotics. This theory combines heuristic theory and hermeneutic theory. This theory is used to find out the hidden meaning conveyed by the songwriter. This semiotic theory is carried out in the following stages. First, the researcher will read quickly without further analyzing the meaning, only the meaning of the lyrics (heuristics). In this case by translating from Japanese into Indonesian. Followed by analyzing the structure, figure of speech, and other in-depth meaning with repeated reading (hermeneutics). Then conclude the results of the analysis. This Hitchcock song has been watched approximately 73 million times by various groups.